NUTRITION INTERVENTIONS IN PATIENTS WITH CROHN’S DISEASE - Beňová, Eva; Boledovičová, Mária; Krištofová, Erika; Pavelová, Ľuboslava (Ing. Peter Zajác, HACCP Consulting, 2016)
Crohn's disease is a chronic non-specific inflammatory bowel disease of any part of the digestive tract. Patients also have specific problems from the nursing perspective that require intervention of nurses, e.g. in the area of nutrition. The role of a nurse in a specific community lies in supporting public health in the field of prevention, health education, group educational activities and care of the acutely or chronically ill. The regulation tool of nursing practice when providing community care is the documented form of nursing data expressed by means of expert terminology. The Omaha System is a standardised terminology for multi-disciplinary teams providing community care. The objective of the research is to draw attention to the possibility of using standardised terminology of the Omaha System when supporting public health in patients with Crohn’s disease with nutrition problems. The research was divided into 3 stages: in the first stage we assessed the nutrition problem in 100 patients dispensarised in gastroenterology counselling centres using a form from the Omaha System. Out of these, identified 42 patients suffered from Crohn’s disease and had problems with nutrition; in the second stage we chose interventions for nutrition from the Intervention Scheme of the Omaha System: their efficiency in patients was assessed by a nurse/nutritionist in the third stage of the research when the patients came to the gastroenterology counselling centre using Problem Rating Scale for Outcomes. When comparing the initial and final nutrition assessment with socio-demographic indicators we found a statistically significant difference (p = 0.000) between the status assessment where women scored a more remarkable advance than men when comparing the initial and the final assessment. With respect to age groups, education and jobs, no statistically significant differences were found (p >0.05).
Keywords: Crohn’s disease; The Omaha System; Nutrition; Interventions; Outcomes